Histopathological Evaluation of Wound Healing and Anti-Inflammatory Effects of Granola Potato Peel Ethanol Extract in Rat Oral Mucosa - Santoso AW; Amalia E; Sari KI; Takarini V; Sufiawati I (Dove Medical Press, 2024)
Astrid Widhowaty Santoso,1,* Eri Amalia,2,* Kartika Indah Sari,3 Veni Takarini,4 Irna Sufiawati5,* 1Oral Medicine Residency Program, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 3Department of Oral Biology, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 4Department of Dental Material Science and Technology, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 5Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Irna Sufiawati, Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Jalan Sekeloa No. 1, Bandung, West Java, 40132, Indonesia, Tel +62-22-2504985, Email irna.sufiawati@unpad.ac.idIntroduction: Oral mucosal wounds present significant clinical challenges due to their susceptibility to infection, inflammation, and delayed healing. The limitation of standard anti-inflammatory drugs (both steroidal and non-steroidal) highlights the urgent need for plant-derived alternative therapies. Granola potato (Solanum tuberosum L.) from Pangalengan, West Java, Indonesia, has shown promise due to its bioactive compounds. However, its potential for wound healing and anti-inflammatory effects, specifically for oral mucosal wounds, remains largely unexplored.Purpose: To evaluate the wound healing and anti-inflammatory activity of Granola potato peel ethanol extract (GPPEE) on the oral mucosa of Wistar rats based on histopathological analysis.Materials and Methods: Forty-eight Wistar rats were wounded on the palatal mucosa using a 4 mm punch biopsy and subsequently divided into four groups: placebo gel, 0.1% triamcinolone acetonide ointment (TCA), 4% GPPEE gel, and 6% GPPEE gel. The rats were euthanized on days 0, 1, 3, 7, and 14. Histopathological parameters assessed included fibroblast proliferation, collagen deposition, angiogenesis, and the presence of inflammatory cells.Results: Phytochemical screening revealed the presence of phenolic compounds, flavonoids, tannins, and alkaloids in the Granola potato peel ethanol extract (GPPEE). Significant differences in the number of inflammatory cells were observed on days 1, 3, 7, and 14 (p< 0.05), with the groups treated with 4% and 6% GPPEE gel initially exhibiting pro-inflammatory effects on day 3, followed by significant anti-inflammatory effects on days 7 and 14. The 6% GPPEE gel treatment demonstrated a notable increase in fibroblasts on days 1, 7, and 14 (p< 0.05), as well as collagen deposition on days 7 and 14 (p< 0.05). However, no significant difference was observed in angiogenesis (p> 0.05).Conclusion: The application of 4% and 6% GPPEE gel demonstrated superior wound healing efficacy compared to 0.1% TCA and exhibited comparable anti-inflammatory activity to 0.1% TCA.Keywords: anti-inflammatory, granola, oral ulcer, potato peel extract, Solanum tuberosum, wound healing